Odpowiedź :
[tex]7)\\\\E=\frac{mv^2}{2}\ \ |*2 \\\\2E=mv^2\ \ |:v^2\\\\m=\frac{2E}{v^2}\\\\[/tex]
[tex]8)\\\\ x- \frac{8x+1 }{2}= \frac{1}{3}\ \ |*6\\\\6x-3(8x+1)=2\\\\6x-24x-3=2\\\\-18x=2+3\\\\-18x=5\ \ |:(-18)\\\\x=-\frac{5}{18}[/tex]
Szczegółowe wyjaśnienie:
7.
[tex]E=\frac{mv^{2} }{2}\:\:\:\:\:\:\:|*2\\\\2E=mv^{2}\:\:\:\:\:\:\:|:v^{2} \\\\\frac{2E}{v^{2}} =m[/tex]
8.
[tex]x-\frac{8x+1}{2} =\frac{1}{3}\:\:\:\:\:\:\:|*6\\\\6x-3*(8x+1)=2\\\\6x-24x-3=2\\\\-18x=5\:\:\:\:\:\:\:\:|:(-18)\\\\x=-\frac{5}{18}[/tex]